Di(2-ethylhexyl) phthalate and dibutyl phthalate have a negative competitive effect on the nitrification of black soil. (April 2022) - Tao, Yue; Feng, Chong; Xu, Jiaming; Shen, Lu; Qu, Jianhua; Ju, Hanxun; Yan, Lilong; Chen, Weichang; Zhang, Ying
Abstract: Di (2-ethylhexyl) phthalate (DEHP) and dibutyl phthalate (DBP) are the most widely used plasticizers for agricultural mulching films and one of the most common organic pollutants in black soil. However, little is known about the effect of these two contaminants on nitrification in black soil. This study investigated the changes of 20 mg/kg DEHP and DBP on the diversity of nitrification microbial communities, the abundance of ammonia oxidizing bacteria (AOB) and nitrite oxidizing bacteria (NOB) related genes, and the activities of key enzymes involved in nitrification. During ammonia oxidation, DEHP and DBP had uncompetitive inhibition of urease, reducing the copy number of amoA gene, and microorganisms ( Azoarcus, Streptomyces and Caulobacter ) would use inorganic nitrogen as a nitrogen source for physiological growth. During nitrite oxidation, the copy number of nxrA gene also reduced, and the relative abundance of chemoautotrophic nitrifying bacteria ( Nitrosomonas and Nitrobacter ) decreased. Moreover, the path analysis results showed that DEHP and DBP mainly directly or indirectly affect AOB and NOB through three ways. These results help better understand the ecotoxicological effects of DEHP and DBP on AOB and NOB in black soil. Graphical abstract: Image 1 Highlights: DEHP and DBP have a negative competitive impact on the ammonia oxidation. DEHP and DBP have a greater impact on inorganic nitrogen than enzymes. Actinobacteria may be affected first and play a major role in microbial functions.